Development of Colour Jump Ball Learning Media to Introduce Colour and Geometric Shapes in Early Childhood - Maharani, Swasti; Hadi, Fida Rahmantika; Afifah, Sofia Nur; Septyawan, Addy; Adamura, Fatriya; Astuti, Indra Puji; Pebriana, Putri Hana (LP. Ma'arif Janggan Magetan, 2025)
This research aims to develop and test the effectiveness of Color Jump Ball as a learning medium in introducing the concept of color and geometric shapes to early childhood. The method used is research and development (R&D) with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the study were 15 children aged 3–4 years who attended TAUD Saqu Madiun. The object of the research is an innovative learning medium in the form of Color Jump Ball. Data was collected through questionnaires, interviews, and observations. The validation results showed that this media is very feasible to use, with a validity rate of 93% of the subject matter experts and the validity of the media experts of 94%. The practicality test showed a significant increase, from 70.20 in the initial field trial to 90.36 in the main field trial. The effectiveness test using the t-test yielded a calculated t-value of 8.516, far exceeding the t-table of 0.443, indicating that the use of Color Jump Ball is effective in improving color recognition and geometric shapes in early childhood. The main contribution of this research is the development of educational learning media that is innovative, interactive, and easy to apply in the context of early childhood education. Color Jump Ball has proven to be not only valid and practical, but also effective in supporting children's cognitive development in the basic aspects of color recognition and shapes.